A review of the active industrial area at Pasir Gudang area, Johore: Some notes and knowledge gaps - Chee Kong Yap; Nur Faradilla Mohd Sabri; Krishnan Kumar; Mohamad Saupi Ismail; Rosimah Nulit; Hideo Okamura; Yoshifumi Horie; Meng Chuan Ong; Ahmad Dwi Setyawan; Chee Wah Yap; Hishamudin Omar; Kennedy Aaron Aguol; et al. (Asia Pacific Academy of Science Pte. Ltd., 2024)
This study aimed to examine the literature on Pasir Gudang, analyse the gathered material, and identify areas lacking knowledge. The literature research reveals that the published studies may be classified into hydrological, monitoring and forecasting, social, economic, and environmental issues. Nevertheless, the subjects of conservation, preservation, pollution recovery, and bioremediation, particularly environmental, social, and governance (ESG) concerns, have been of recent interest. Thus, these information gaps are strongly advised to be addressed in future research in and around the busy Pasir Gudang industrial sector.